INNOVATION STRATEGIES AND COOPERATION FOR REGIONAL TOURISM DEVELOPMENT - Zontek, Zbigniew; Lipianin-Zontek, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2010)
The aim of this article is to indicate the directions of the development of tourist sector innovativeness in the region. In the article was self-characterized the essence of the innovation strategies, used both by tourist enterprises and institutions supporting the development of tourism. It was showed, that tourist enterprises seeking possibilities of introducing new solutions, both products as process, deserve on the name of innovative. There were presented these international organizations, which favour the co-operation in the field of tourism and creating innovative actions. There were also showed the chosen results of research in Poland with special pressure on the indexes of trade and the economy of tourist.